An audit of HIV treatment outcomes in a UK inner city cohort. (October 2016) - Bird, E; Cormack, I; Rodgers, M; Phillips, D; Elgalib, A
We describe the demographics and treatment outcomes of a HIV-infected cohort from Croydon University Hospital, London, UK. We showed that the Croydon Cohort had good viral load suppression (98.6% with viral load < 100 copies/ml and 99.0% with viral load < 200 copies/ml) despite being a potentially challenging cohort in a deprived area of London. The viral load outcomes are better than the Public Health England data from 2014 and the latest British HIV Association audit using data from 2009.